Implementation of Decentralized Water Resources Management Based on Integrated Water Resources Management in Indonesia (A Case Study of Cisadane River Basin) - Djamres, Eilif Kurnia Deda (FIA UB, 2018)
Currently, many countries in the world have been implemented decentralization for its water resources management. It is convinced that decentralization can improve people welfare and reach sustainable water resources. Since the last two decades, Indonesia has been performed decentralization for managing water resources. However, some problems related to water management still exist such as flood, drought, and ego sectoral among stakeholders. Cisadane river basin as one of national strategic river basin faced the fastest growing population and land conversion function in Indonesia. Some conflicts occurred not just between people in upstream and downstream area but also among stakeholders. This research is a case study descriptive study with a qualitative approach. Using Grindle model, we analysed the performed of the decentralization and elaborated the supporting and constraining factors in the implementation. As a result, in general, application of decentralized water resources management based on integrated water resource management principles at Cisadane river basin has been running well. Nevertheless, some problems related communication and collaboration among stake holders, public participation, and budget are the main issues of decentralized water resources management in Indonesia and can hamper the policy to reach its goals.